The determinants of health status in a developing country : Results from the Colombian Case (2005)
The estimation of the determinants of health status is an important input for public policy. It helps to understand the risk of specific habits and its effects in productivity and economic growth (Savedoff and Schultz 2000). It also brings information to the policy makers about the effects of particular public strategies in the health condition of the population (Gerdtham et al. 1999).-- Introducción